CIBERER: Spanish national network for research on rare diseases: A highly productive collaborative initiative. Issue 5 (4th February 2022) - Luque, Juan; Mendes, Ingrid; Gómez, Beatriz; Morte, Beatriz; López de Heredia, Miguel; Herreras, Enrique; Corrochano, Virginia; Bueren, Juan; Gallano, Pía; Artuch, Rafael; Fillat, Cristina; Pérez‐Jurado, Luis A.; et al.
Abstract: CIBER (Center for Biomedical Network Research; Centro de Investigación Biomédica En Red ) is a public national consortium created in 2006 under the umbrella of the Spanish National Institute of Health Carlos III (ISCIII). This innovative research structure comprises 11 different specific areas dedicated to the main public health priorities in the National Health System. CIBERER, the thematic area of CIBER focused on rare diseases (RDs) currently consists of 75 research groups belonging to universities, research centers, and hospitals of the entire country. CIBERER's mission is to be a center prioritizing and favoring collaboration and cooperation between biomedical and clinical research groups, with special emphasis on the aspects of genetic, molecular, biochemical, and cellular research of RDs. This research is the basis for providing new tools for the diagnosis and therapy of low‐prevalence diseases, in line with the International Rare Diseases Research Consortium (IRDiRC) objectives, thus favoring translational research between the scientific environment of the laboratory and the clinical setting of health centers. In this article, we intend to review CIBERER's 15‐year journey and summarize the main results obtained in terms of internationalization, scientific production, contributions toward the discovery of new therapies and novel genes associated to diseases, cooperation with patients' associations and many other topics related to RD research. Abstract :